2019
DOI: 10.1049/iet-cds.2018.5263
|View full text |Cite
|
Sign up to set email alerts
|

Resource‐efficient FPGA implementation of perspective transformation for bird's eye view generation using high‐level synthesis framework

Abstract: Bird's eye view (BEV) generation from front-looking video stream is considered an important pre-processing task in various computer vision applications such as driver assistance systems. In this work, hardware implementation of this process using high-level synthesis in Simulink environment has been considered for rapid prototyping under real-time constraints. Traditionally, researchers have employed lookup table-based approaches to circumvent the exorbitant cost of implementing arithmetic modules associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…An integrated tool flow for simulating and generating HDL for computer vision algorithms was created in 2019 with the advent of the Vision HDL Toolbox which allows one to convert images composed of rows and columns into pixel streams that can be processed at the pixel line rates. Bilal et al demonstrated the use of this new toolbox by implementing a perspective transformation for bird's eye view generation [18].…”
Section: Related Workmentioning
confidence: 99%
“…An integrated tool flow for simulating and generating HDL for computer vision algorithms was created in 2019 with the advent of the Vision HDL Toolbox which allows one to convert images composed of rows and columns into pixel streams that can be processed at the pixel line rates. Bilal et al demonstrated the use of this new toolbox by implementing a perspective transformation for bird's eye view generation [18].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the hardware design scheme is given, which can solve the optical distortion and perspective distortion to a certain extent. The homography transformation method is used in [19][20][21], which needs to be realized by matrix multiplication, and different transformation matrices can realize different perspective transformations. The result obtained by this method is more in line with the observation habits of the human eye, but the solution of the transformation matrix needs to solve the 8-variable linear equation system, which is extremely difficult for hardware.…”
Section: Analysis Of Performancementioning
confidence: 99%
“…Moreover, Refs. [19][20][21] are all implemented on the Field Programmable Gate Array (FPGA), which are used to generate the Bird's-Eye View (BEV), correction of input video from two cameras, and obstacle detection, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations